Application of Clam (lokan) Shell as Beach Retaining Wall - Yusof, M.; James Ujai, S.J.; Sahari, F.; Taib, S.N.L.; Noor Mohamed, N.H. (2011)
This project is about investigating the possibility of using the local clam (lokan)l embedded in the concrete as beach retaining wall. Since the shell is considered as undesirable product and normally disposed in open area, the researchers taking this opportunity to determine the possibility of lokan shell powder as the alternative fine aggregate to increase the compressive strength of the concrete. From the compression test, by embedding lokan powder into the concrete, it can increase the compressive strength up to 16% (at 30 wt% of lokan powder) compared to concrete without lokan powder. Thus, it can be concluded that lokan powder which is waste material has high potential as the alternative fine aggregate to improve strength of the concrete and can be applied as a retaining wall